(untitled) (Simbiótica. Revista Eletrônica, 2022)
The present photographic essay offers a “burning” and enchanted lens of popular culture from Espírito Santo, particularly the “congo”, as a possibility of a seam – territorialized and territorializing – of diverse times, spaces in transformation, emotions and perceptions. Keywords: Photography; Love; Congo; Capixaba.